3D Rapid Prototyping for Synchrotron Application - Ryan, Christopher H.; Wysokinski, Thomasz W.; Chapman, L. Dean; Korbas, Malgorzata (CMBES Proceedings, 2007)
The Biomedical Imaging and Therapy (BMIT) Beamlines at the Canadian Light Source (CLS) is designed for the purpose of imaging and radiation therapy research both with animals ranging from mice to horses and humans. Being the only beamline in the world with this capacity, BMIT will be continuously encountering unique problems requiring innovative solutions. 3D rapid prototyping has proven to be one of the possible solutions. There are a variety of applications for 3D rapid prototyping (RP) in the Synchrotron environment. At BMIT, rapid prototyping will be the primary concentration for fabrication of unique and difficultly machined precision instruments and animal restraints. The designing and manufacturing process of such unique components includes: 1. Development of 3D model of part which could include an x-ray CT or MRI scan of animal. 2. Conversion of model or scanned data to CAD formats. 3. Fabrication of unique component using 3D printer. Conventional prototyping techniques are expensive, time consuming and dated. With late advancements in 3D printing, scanning, and CAD software, the task of 3D-RP is becoming more readily available, cost effective, accurate and provides quick turnaround. This paper describes the current and future technologies of each process, which will be implemented at the BMIT beamlines to ensure maximum resolution image quality, while improving efficiency and reducing stress on the animals.